1994
DOI: 10.1016/0741-5214(94)90278-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of improved hemodynamics on aortic dimensions in patients undergoing heart transplantation

Abstract: Of 68 heart transplant patients prospectively evaluated, aortic diameter increased in 31 (46%); new aneurysms developed in four of these patients. Greater incremental increases in cardiac ejection fraction were significant correlates with aortic enlargement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…11-16 Following heart transplantation reported growth rates have ranged from 0.74 to 2.1 cm/year. 1,2,4,6,9,24 This published experience is similar to that of the present study where the mean aneurysm growth rate was 1.2 cm/year following OHT. Several studies have attributed the faster aneurysm growth rate in OHT patients to the use of corticosteroid immunosuppressive regimens.…”
Section: Discussionsupporting
confidence: 92%
“…11-16 Following heart transplantation reported growth rates have ranged from 0.74 to 2.1 cm/year. 1,2,4,6,9,24 This published experience is similar to that of the present study where the mean aneurysm growth rate was 1.2 cm/year following OHT. Several studies have attributed the faster aneurysm growth rate in OHT patients to the use of corticosteroid immunosuppressive regimens.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the presence of a strong new donor heart along with the collagen weakening effect of immunosuppression may have detrimental effects on the inherently weakened aorta. This concern is also supported by the observation of an increased incidence and a more aggressive course of abdominal aortic aneurysms in transplant recipients (both heart and abdominal organ transplantations) 14 15. There are no evidence-based guidelines for adequate preventive treatment of the weakened aorta in this specific case but it has been demonstrated that the need for reintervention in the distal aorta of patients with MFS with previous aortic root surgery is significantly increased in patients with previous hypertension as compared to those without hypertension 16.…”
Section: Discussionmentioning
confidence: 91%
“…The high incidence of arterial hypertension, diabetes mellitus, and accelerated arteriosclerosis caused by immunosuppression predisposes heart transplantation patients to this complication. Of note, accelerated growth of true atherosclerotic aneurysms of the ascending aorta, 10 increased growth of abdominal aortic aneurysms, 11 and increased incidence of perivascular disease 12 have all been reported in heart transplant recipients.…”
Section: Discussionmentioning
confidence: 99%